Role of TNF-α in early-stage fracture healing under normal and diabetic conditions. (January 2022) - Zhang, Enhao; Miramini, Saeed; Patel, Minoo; Richardson, Martin; Ebeling, Peter; Zhang, Lihai
Highlights: Developed a numerical model for investigating TNF-α mediated bone fracture healing. An optimal TNF-α concentration should exist in the fracture callus. Excessive TNF-α could decrease MSCs' concentration at the initial healing stage. Insufficient TNF-α might significantly hinder the healing process. Abstract: Background and objective: Inflammatory response plays a crucial role in the early stage of fracture healing. Immediately after fracture, the debris and immune cells ( e.g., macrophages), recruited into the fracture callus, lead to the secretion of inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), which governs the mesenchymal stem cells (MSCs) mediated healing processes. However, it is still unclear how chronic inflammatory diseases ( e.g., diabetes) affect the level of TNF-α in fracture callus, ultimately the healing outcomes at the early stage of healing. Therefore, the purpose of this study is to develop a numerical model for investigating TNF-α mediated bone fracture healing. Methods: A mathematical model consisting of a system of partial differential equations that represent the reactive transport of cells and cytokines in the fracture callus is developed in this study. The model is first calibrated by using available experimental data and then implemented to study the effect of TNF-α on the early stage of fracture healing under normal and diabetic conditions. Results: There is a significant elevation of TNF-α level in facture callus during the first 24 h post-fracture in normal condition, and its influence in the concentration of MSCs and cell differentiation becomes significant three days post-fracture ( e.g., the absence of TNF-α signaling could reduce the concentration of MSCs more than 20% in cortical callus). In addition, the excessive secretion of TNF-α induced by diabetes could decrease the concentration of MSCs at the initial stage of healing, particularly reduce the concentration of MSCs in cortical callus by around 25%. Conclusion: The model predictions suggested that there should be an optimal concentration of TNF-α in fracture callus, which enhances the early stage of healing, and excessive or insufficient secretion of TNF-α might significantly hinder the healing process.